The CO hydrogenation on Co/SBA-15 and Co/Al2O3 catalysts. - Abreu, Thiago Ferreira de (2022)
Worldwide there is an increasing demand for primary energy sources (PES). The current scenario suggests a low-rate shift of PES using clean fossil fuels, in particular natural gas (NG) and renewable energy sources, which also impacts the chemical industry. In this context, the gas-to-liquids (GTL) process may play a strategic role on this transition. The CO hydrogenation reaction, which is the core of this technology, leads to the production of many products, such as paraffins and olefins, from syngas (H2+CO). The Fischer-Tropsch Synthesis (FTS) is limited by many critical factors, so efficiency improvements through catalyst design and lifetime is mandatory to provide higher competitiveness to the technology. In this study, the performance of cobalt-based catalyst for the CO hydrogenation reaction was evaluated, using -alumina and SBA-15 supports, aiming at understanding the operating condition effects. The evaluated supports and catalysts were synthesized and characterized for textural, morphological and structural properties assessment. The effects of temperature and space velocity over the 15% Co/SBA-15 and 15% Co/-Al 2O3 catalysts were evaluated in terms of activity, selectivity to lower olefins (C2=-C4=) and C5+ selectivity. The catalyst deactivation with time-on-stream (TOS) was also evaluated in terms of carbon formation by TGA/DTA and Raman spectroscopy techniques. Overall, results show that both catalysts produced paraffins as main product and presented a higher activity at lower space velocity and higher temperature and higher selectivity to higher hydrocarbons (HC) and lower olefins at lower space velocity and lower temperature. From the tested catalysts, the 15% Co/SBA-15 presented higher activity and selectivity to lower HC up to the gasoline range, with a slightly higher selectivity to lower olefins, whereas the 15% Co/-Al2O3 produced higher HC according to the C5+ selectivity. Two deactivation stages with similar carbon depositions were detected for both catalysts. Differences in yield loss with TOS can be explained by the carbon migration phenomenon.